Do we Still Need a Veno-Venous Bypass Service in Liver Transplantation? A Survey of UK Practice. (July 2018) - Strachan, Alexa; Hannon, Vivienne; Melikian, Clare N
Abstract : Introduction: With advancements during liver transplantation (LT), specifically surgical refinements, the necessity of veno-venous bypass (VVB) in LT has been previously questioned in the literature and there is limited evidence to guide clinicians when developing or maintaining a VVB service. A 2011 Cochrane review[1] concluded there was 'no evidence to support or refute the use' of VVB based on 3 trials with a 'high risk of bias'. However, in 2015 a new service in Germany[2] published a set of 163 pts undergoing LT with VVB reporting lower rates of acute kidney injury (AKI) and 'post-reperfusion syndrome' without significant VVB morbidity and Sun at al[3] demonstrated the use of VVB in patients with renal compromise resulted in improved post-operative renal function. With this knowledge, we undertook a survey of UK practice of LT centres to describe the present use of VVB in transplant. Methods: We sent email surveys to all seven UK transplant centres and received four responses. Results: There is great variation of practice within the UK with half of the responding centres regularly using VVB, or having the service on standby, for selected cases in both LT and hepatobiliary surgery. The remaining two centres no longer have the infrastructure or requirements for a VVB service for Cardiothoracic surgery. Conclusions: We believe the question as to whether a VVB service improves outcomes in LT and is therefore required as part of the infrastructure in a LT centre remains unanswered. Given the substantial morbidity and mortality associated with VVB, we suggest work to strength the evidence base surrounding its use is required before further developing a VVB service in centres without it. [1] Gurusamy KS, Koti R, Pamecha V, Davidson BR, Veno-venous bypass versus none for liver transplantation, Cochrane database of Systematic Reviews 2011, Mar 16.3.:[007712]. DOI: [10.1002/14651858] [2] Mossdorf et al, Bypass during Liver Transplantation: Anachronism or Revival?, Gastroenterol Res Pract. 2015; Mar 2. Doi: 10.1155/2015/967951. [3] Sun K et al, Venovenous Bypass is Associated with a Lower Incidence of Acute Kidney Injury After Liver Transplatation in Patietns with Compromised Pretransplant Renal Function, Anesth Analg, 2017 Nov; 125(5): 1463-1470.